Laser powder bed fusion of polyamide-composite for antibacterial applications: Characterization and properties. (June 2022) - Vilardell, Anna Martin; Yadroitsava, Ina; Wolf, Winston Kagisho Curtis; Du Plessis, Anton; Tshibalanganda, Muofhe; Kouprianoff, Dean-Paul; Garcia-Giralt, Natalia; Kobashi, Makoto; Yadroitsev, Igor
Abstract: Additive manufacturing (AM) components can benefit medical applications by improving their functionality and/or providing well fit custom designs. Metal and polymer AM potential can be perfectly expanded to composite materials, such as metal-ceramics, polymer-ceramics, polymer-metal, etc. These components have unique properties that can be beneficial in a variety of end-use industries. The present investigation focuses on the manufacturing and characterization of polyamide-copper composite produced by in-situ laser powder bed fusion, with Cu as a bactericidal agent to reduce risk of infection. A black polyamide PA12/B powder was chosen as a polymer-base to be directly mixed with 10 and 20 wt% Cu contents. A well-studied AM PA2200 material was chosen as a reference material. A characterization study by means of surface roughness, porosity and mechanical properties has been performed. Results showed that the characteristic and properties of the newly developed composite are appropriate and highly promising for medical applications. Graphical Abstract: ga1